2022
DOI: 10.3389/fpls.2022.792079
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Expression Analysis of Root Tips in Contrasting Rice Genotypes Revealed Novel Candidate Genes for Water Stress Adaptation

Abstract: Root system architecture (RSA) is an important agronomic trait with vital roles in plant productivity under water stress conditions. A deep and branched root system may help plants to avoid water stress by enabling them to acquire more water and nutrient resources. Nevertheless, our knowledge of the genetics and molecular control mechanisms of RSA is still relatively limited. In this study, we analyzed the transcriptome response of root tips to water stress in two well-known genotypes of rice: IR64, a high-yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 137 publications
0
17
0
Order By: Relevance
“…A recent genome-wide association study (GWAS) on the roots of two contrasting rice varieties under drought revealed 288 differentially expressed genes from the families of NAC, AP2/ERF, AUX/IAA, EXPANSIN, WRKY, and MYB (Abdirad et al, 2022). This finding warrants further research into verifying the roles of these genes in the differential RSA responses to water stress as one variety enhanced growth and root exploration to access water to avoid water deficit, whereas the other relied on cell insulation to maintain water and antioxidant system to withstand water stress (Abdirad et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…A recent genome-wide association study (GWAS) on the roots of two contrasting rice varieties under drought revealed 288 differentially expressed genes from the families of NAC, AP2/ERF, AUX/IAA, EXPANSIN, WRKY, and MYB (Abdirad et al, 2022). This finding warrants further research into verifying the roles of these genes in the differential RSA responses to water stress as one variety enhanced growth and root exploration to access water to avoid water deficit, whereas the other relied on cell insulation to maintain water and antioxidant system to withstand water stress (Abdirad et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Potential marker genes involved in sugar metabolism, root growth and elongation were identified in our previous transcriptome studies on two rice genotypes with different drought tolerance [ 31 , 32 ]. Thirteen genes were selected as candidate markers, and their expression levels were measured by qRT-PCR in the roots of the two genotypes grown under control and drought stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our previous miRNA-seq and mRNA reports [ 31 , 32 ], 13 genes involved in root growth and elongation and regulation of root primary metabolism were selected. Total RNA isolation was done using the TRIzol reagent (BioBasic-BS410A, Canada) as per the manufacturer’s guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a previous GWAS study revealed the wheat NAC gene (i.e., TaNAC071-A ) was closely associated with drought tolerance, i.e., the knockdown of TaNAC071-A attenuated drought tolerance of wheat, whereas its overexpression significantly enhanced drought tolerance through improved water-use efficiency and increased expression of stress-responsive genes [ 79 ]. Another genome-wide expression analysis in rice revealed novel candidate genes involved in water stress adaptation, including members in the families of NAC, AP2/ERF, WRKY, and MYB playing important roles in drought adaptation [ 80 ]. These results indicated that the identification of these QTLs and genes involved in drought tolerance would significantly facilitate the molecular breeding of drought tolerant soybean plants.…”
Section: Discussionmentioning
confidence: 99%